Pelatihan Media Pembelajaran Kotak Huruf Hijaiyyah pada Guru RA Nurul Islam Desa Gung Pinto - Intan Syahdila Hasibuan; Oisthina Hasibuan; Ni Komang Nandhita Dharma Santy; Ulvia Nisa Ansari; Ahmad Syukri Sitorus; Khairani Tambunan; Silvia Anggraini; Siti Khodijah Nasution; Tiara Angelly (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The availability of learning media at RA Nurul Islam in Gung Pinto Village is very minimal, this is influenced by two factors, namely: the distance is difficult and far, and the educators who teach at the RA are also not in accordance with their fields. These two things are the inhibiting factors for the emergence of educator creativity to improve the ability of aspects of child development. The purpose of this study was to increase the creativity and innovation of educators in making learning media from used materials, how to apply and explain learning media to the children of RA Nurul Islam in Gung Pinto Village. This study uses a qualitative approach with data collection techniques, namely interviews, observation and documentation. From the observations we have made at RA Nurul Islam, Gung Pinto Village, there are educators who are participants in the training for making hijaiyyah letter box learning media. The results of this study are, 1) increasing the understanding of educators about making hijaiyyah letter box learning media, 2) increasing educator creativity and innovation in making learning media from used materials, 3) educators are expected to be able to implement hijaiyyah letter box learning media in the learning process. 4) provide knowledge to early childhood about hijaiyyah letters. Keywords: Creation and application, Early Childhood, Hijaiyyah letter box media